Short web documentary is an original artistic form interview with Charlie Phillips - Česálková, Lucie (Iluminace, 2016)
Interview with Charlie Phillips, who selects documents for the website of the British newspaper The Guardian. The interview was conducted on the occasion of this year's International Documentary Film Festival in Jihlava.
Keywords: editor and producer; internet and film; documentary; journalists and film; press and film